2013
DOI: 10.1186/2193-1801-2-247
|View full text |Cite
|
Sign up to set email alerts
|

Study of photosynthetic pigments changes of maize (Zea mays L.) under nano Tio2 spraying at various growth stages

Abstract: Tests were done on the effects of treatments of titanium dioxide spray on corn (Zea mays L.). The study was conducted as a factorial experiment in a randomized complete block design with four replications. Treatments consisted of two factors; the first factor was stage of plant growth that spraying was applied (vegetative stage, appearance of male flowers and female flowers); and the second factor was that of different concentrations of titanium dioxide nanoparticles (Tio2) that consisted of spray with water (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
71
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 168 publications
(92 citation statements)
references
References 11 publications
10
71
1
Order By: Relevance
“…It has been documented that plants under optimum condition tend to increase growth period as much as possible which can result in improved leaf photosynthesis, light-use potential and higher yield (Cui et al, 2015). This study showed that nano-fertilizers and nano TiO 2 considerably influenced the straw (SY) and grain yield (GY), which corroborate the findings of a great deal of the previous work (Gao et al, 2013;Morteza et al, 2013;Klingenfuss, 2014;Tarafdar et al, 2014). Foliar utilization of micronutrients improved straw yield and grain yield up to 7 % and 16 % over to control, respectively.…”
Section: Resultssupporting
confidence: 81%
See 3 more Smart Citations
“…It has been documented that plants under optimum condition tend to increase growth period as much as possible which can result in improved leaf photosynthesis, light-use potential and higher yield (Cui et al, 2015). This study showed that nano-fertilizers and nano TiO 2 considerably influenced the straw (SY) and grain yield (GY), which corroborate the findings of a great deal of the previous work (Gao et al, 2013;Morteza et al, 2013;Klingenfuss, 2014;Tarafdar et al, 2014). Foliar utilization of micronutrients improved straw yield and grain yield up to 7 % and 16 % over to control, respectively.…”
Section: Resultssupporting
confidence: 81%
“…Besides the same research reported a positive effect of nano-titanium on chlorophyll content in wheat seedling. These findings further support the idea of Morteza et al, (2013) that foliar utilization of nTiO 2 can improve plant growth and grain yield by facilitating the manufacture of pigments and transformation of light energy to active electron and chemical activity and increases photosynthetic efficiency. .32 SL=spike length (cm), TGW=1000 grain mass (g), DA= days to anthesis, DM= days to maturity, CHL= chlorophyll content (SPAD unit), GY= grain yield (Kg ha -1 ), SY= straw yield (Kg ha -1 ), HI= harvest index (%).…”
Section: Resultssupporting
confidence: 73%
See 2 more Smart Citations
“…nTiO 2 increases plant growth by enhancing nitrogen metabolism (Yang et al, 2006) which improves the absorption of nitrate in spinach, and also by accelerating the conversion of inorganic nitrogen into organic nitrogen which increases the fresh and dry masses. Morteza et al (2013) suggested that foliar utilization of nTiO 2 can improve plant growth and grain yield by improving the biosynthesis of pigments and conversionof light energy to chemical energy, thereby increasing photosynthetic efficiency. Effects of nTiO 2 on the content of light harvesting complex II (LHC II) on thylakoid membranes of spinach increases LHC II content Lei et al, 2007).…”
Section: Discussionmentioning
confidence: 99%